Comparison of the efficiencies of customized CSA-and rlectin-elisas for detection of anti-amoebic antibody based on selected aborigines serum samples - AlTameemi, Abeer Muataz Abed (2018)
Orang Asli, the Malaysian aborigines live in remote jungles, are endemic for amoebiasis. Understanding the disease prevalence and distribution is important for the control and preventive measures. A major indicator that reflects on the disease incidence is the presence of highly elevated anti-amoebic antibody. However, continuous screening of the antibody using commercial kits is impractical due to the high cost. Cheaper but valid in-house customized assay should be employed instead to attain cost-effective and sustainable outcome. Hence, the presence study aimed to compare the efficiencies of customized crude soluble antigen (CSA)-ELISA and recombinant lectin (rLectin)- ELISA for detection of anti-amoebic antibody in selected Orang Asli serum samples, which were prior defined by commercial indirect haemagglutination assay (IHA). CSA was produced from axenically grown Entamoeba histolytica trophozoites, while rLectin was overexpressed and purified from Escherichia coli harbouring the corresponding recombinant gene. For the development of the two customized ELISAs, antigen concentration, serum and conjugated antibody dilutions were optimized. The efficiencies of both customised ELISAs were determined by 30 positive and negative serum samples pre-determined by commercial IHA. According to receiver operating characteristics (ROC) curve analysis, both customized ELISAs showed excellent diagnostic performances. As compared to the reference assay, the positive percentage agreement of CSA-ELISA (91%) was higher than that of rLectin-ELISA (61%), whileboth ELISAs showed the same negative percentage agreement, which was 97%. According to analysis of ELISA ODs, the positive delta value for CSA-ELISA (0.4472) was higher than that of rLectin-ELISA (0.2673), while the negative delta value of rLectin-ELISA (-1.209) was lower than that of CSA-ELISA (-1.175). In conclusion, this study demonstrated that CSA-ELISA was more sensitive in detecting the presence of anti-amoebic antibody, while rLectin-ELISA was more specific in ruling out negative cases.